Everyday work investigations for safety. (4th March 2018) - Havinga, Jop; Dekker, Sidney; Rae, Andrew
ABSTRACT: A key theme in safety is the investigation and improvement of work processes and conditions. This is built on a tradition of studying accidents, but there is growing interest in the investigation of everyday work. Researchers have started using terms such as success, normal and everyday work investigations, but behind these can be different activities. This paper makes explicit some considerations behind investigations of everyday work, how these considerations shape an investigation, and how they reflect different schools of thought. These considerations can be used as an aid for designing everyday work investigations for safety and serve as a first step towards critical reflection on investigating everyday work.